Codeine Ultra-rapid Metabolizers: Age Appears to be a Key Factor in Adverse Effects of Codeine - Heintze, K.; Fuchs, W. (Drug Research, 2015)
Codeine is widely used as an analgesic drug. Taking into account the high consumption of codeine, only few fatal adverse events have been published. A number of reports, where neonates and children showed serious or fatal adverse reactions, led to a restriction of the use of codeine in this patient group. Therefore, we reviewed the safety of codeine in adults. PubMed was systematically searched for clinical studies and case reports, with a special focus on CYP2D6, the enzyme that converts codeine to morphine and exhibits genetic polymorphism.181 cases were identified in adults in conjunction with serious or lethal effects of codeine. In the vast majority of cases, codeine was used in combination with other drugs by drug-dependent individuals or with a suicidal intent. Only 2 cases were found where ultra-rapid metabolizers experienced severe non-lethal adverse events. This is far less than would be predicted from the number of cases reported in children. The discrepancy may be explained by developmental changes in the disposition of codeine.The strategy of regulatory authorities to restrict access to codeine for infants and young children, the apparent highest risk group, has a factual and pharmacological rationale. By the same standards, there is no need for restrictions for adult use of codeine.
Keywords: codeine; ultra-rapid metabolizers; adults; children; CYP2D6; CYP3A4